THE MODERN FOREIGN POLICY OF RUSSIA AND THE U.S.A. IN THE MIDDLE EAST - Ivan Fiodorovich Khudyakov (Вестник Северо-Кавказского федерального университета)
This article focuses on Russian foreign policy and the U.S. in the Middle East. During the writing of a comprehensive analysis of the Middle East region, as well as assessment of prospects for increased regional foreign policy positions of the Russian Federation.